The Impacts of Dietary Curcumin on Innate Immune Responses and Antioxidant Status in Greater Amberjack (Seriola dumerili) under Ammonia Stress - Chuanpeng Zhou; Zhong Huang; Shengjie Zhou; Jing Hu; Rui Yang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma (Journal of Marine Science and Engineering, 2023)
In this study, we investigated the effect of dietary curcumin on non-specific immune responses and antioxidative ability in Seriola dumerili under ammonia stress and post-recovery. Three diets were prepared to contain 0, 75, and 150 mg/kg of curcumin. A total of 225 greater amberjack (initial weight: 100.90 ± 0.03 g) were distributed into nine cylindrical tanks, constituting an experimental design with three treatments and three replicates. After 56 days of feeding, plasma, intestinal, and hepatic enzyme activities were evaluated. Then, an acute ammonia challenge experiment was conducted. Ten fish per tank were subjected to acute ammonia stress (total ammonia-N: 1000 mg/L) for eight minutes followed by six minutes of recovery. The results indicated that dietary curcumin significantly promoted intestinal and hepatic alkaline phosphatase (ALP) and acid phosphatase (ACP) levels as well as hepatic antioxidative enzymes such as superoxide dismutase (SOD), total antioxidant capacity (T-AOC), reduced glutathione (GSH), and glutathione peroxidase (GSH-Px) of greater amberjack. In addition, curcumin addition improved the activities of antioxidant enzymes, such as SOD, T-AOC, GSH, GSH-Px, and catalase (CAT), and reduced malondialdehyde (MDA) content in liver, spleen, head kidney, and brain tissues after post-recovery. The indexes related to immunity and antioxidant enzymes in the liver, gill, and spleen rose again to some extent, but they showed the worst recovery ability in the head kidney and brain tissue samples. These results indicate that dietary curcumin supplementation could increase non-specific immune responses, antioxidant ability, and enhance resistance to high ammonia stress in juvenile S. dumerili.